Comparative study on effects of adding germinated and non‐germinated legumes on bioactive components, antioxidant, textural and sensory characteristics of cereal flakes. Issue 1 (4th January 2021) - Sattar, Dur‐e‐shahwar; Fauqiha, Ayesha tul; Mohamed, Mwanasiti; Ali, Tahira Mohsin; Hasnain, Abid
Abstract: The objective of this study was to prepare healthy breakfast cereal flakes through addition of selected germinated legumes, namely, lentils ( Lens culinaris ), green gram ( Vigna radiata ), and black gram ( Vigna mungo) . Flakes containing germinated legumes were compared in terms of bioactive compounds, texture, moisture content, and sensory properties with flakes made with non‐germinated legumes. It was observed that flakes made with germinated legumes were higher in polyphenols, flavonoids, flavonols, and antioxidant activity with a crispier and more desirable texture. Moreover, shelf life was evaluated on the basis of moisture content and sensory characteristics for 90 days. The best flakes in terms of storage were the ones containing germinated legumes as these were low in moisture content even after 90 days of storage, which is essential for extending the shelf life of the product. These germinated legume containing cereal flakes also received higher scores in terms of sensory characteristics. Incorporation of legumes can thus provide a cheap and healthy snack for people of all ages.